2021
DOI: 10.1016/j.micpath.2021.105108
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of recombinant canine distemper virus that expresses S1 subunit of SARS-CoV-2 spike protein in vitro

Abstract: The coronavirus disease 2019 (COVID-19), as an unprecedented pandemic, has rapidly spread around the globe. Its etiological agent, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), belongs to the genus Betacoronavirus in the family Coronaviridae . The viral S1 subunit has been demonstrated to have a powerful potential in inducing protective immune responses in vivo . Since April 2020, farmed minks were frequently reported to be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The reverse genetics platform of the CDV QN strain was established previously in our laboratory. Using this platform, we have constructed many recombinant CDVs expressing foreign antigens, such as SARS-CoV-2 S1 protein (Liu et al, 2021b) and Dabie bandavirus Gn/Gc (data not shown). In the present study, the rCDV-VP2 was rescued from its cDNA clone using reverse genetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reverse genetics platform of the CDV QN strain was established previously in our laboratory. Using this platform, we have constructed many recombinant CDVs expressing foreign antigens, such as SARS-CoV-2 S1 protein (Liu et al, 2021b) and Dabie bandavirus Gn/Gc (data not shown). In the present study, the rCDV-VP2 was rescued from its cDNA clone using reverse genetics.…”
Section: Discussionmentioning
confidence: 99%
“…This recombinant virus had been subjected to serial passages in vitro, followed by NGS analysis to reveal quantitatively a mutated profile of the passage-47 (P47) progeny (Liu et al, 2021c). More recently, we have constructed another system of CDV reverse genetics based on a vaccine strain (QN strain) (Liu et al, 2021b). Using this system, we rescued here a recombinant CDV that could stably express the CPV-2a VP2 for at least 33 serial passages in cells.…”
Section: Introductionmentioning
confidence: 99%
“…: MT236316) were optimized for codon usage bias in dogs using an online codon-optimizing tool ( https://www.vectorbuilder.cn/tool/codon-optimization.html ), followed by chemical synthesis. These two codon-optimizing sequences were independently subcloned into the Not I/ Pme I sites of another CDV cDNA clone ( 25 ) via homologous recombination using the In-Fusion® Kit (Takara, Dalian, China) according to the manufacturer's instruction. Two recombinant cDNA clones ( Figures 1C,D ) were subjected to Sanger sequencing for confirming their identities, followed by plasmid extraction using the HighPure Maxi Plasmid Kit (TIANGEN, Beijing, China) according to the manufacturer's instruction.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, there has been no report concerning CDV-vectored vaccines against DBV as yet. We had developed one virulence-attenuating strain (CDV QN strain) previously, and more recently, we constructed its reverse genetics platform for expressing foreign antigens ( 24 , 25 ). Considering anti-DBV vaccines unavailable for dogs, we rescued two recombinant CDVs in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously constructed two reverse genetics platforms for different CDV strains. Both platforms facilitate recovery of marker-tagged ( Liu et al., 2020 ) or antigen-expressing ( Liu et al., 2021 ) recombinant CDV. In this study, a recombinant eGFP-tagged CDV (rCDV-eGFP) was rescued, identified, characterized and then used as a model virus for extra forty passages separately in ribavirin- and non-treated cells.…”
Section: Introductionmentioning
confidence: 99%